The syawir method as a cooperative learning model of Islamic religious education in pesantren-based schools - Fathurrohman, Rizal; Gafarurrozi, Muhammad; Prihantoro, Wahyu Kholis (Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to examine the use of the Syawir method as a representation of cooperative learning in PAI learning in Islamic Boarding Schools. This research is library research by taking the analysis and synthesis of several field study articles and literature reviews. The results of the study show that Islamic education learning in Islamic boarding schools is more holistic in terms of both curriculum and material. The Syawir method can be used as a cooperative learning model in the PAI learning process. This is based on the similarity of cooperative learning principles developed by educational experts, such as David and Roger Johnson. The application of Syawir in PAI learning at Islamic boarding schools can be carried out in several stages, namely group formation, assignment, group organizing, discussion, group accountability, evaluation, and reflectionTujuan penelitian ini adalah untuk menganalisis penggunaan metode syawir sebagai representasi pembelajaran kooperatif dalam pembelajaran PAI di Sekolah Berbasis Pesantren. Penelitian ini merupakan penelitian kepustakaan dengan menggunakan sumber pustaka sebagai objek penelitian. Penulis berkonsultasi dan mengambil analisis dan sintesis dari beberapa artikel kajian lapangan dan kajian literatur. Hasil penelitian menunjukkan bahwa pembelajaran PAI di Sekolah Berbasis Pesantren lebih bersifat holistik dari segi kurikulum dan materinya. Metode syawir dapat digunakan sebagai salah satu model pembelajaran kooperatif dalam proses pembelajaran PAI. Hal itu, didasarkan pada kesamaan prinsip-prinsip pembelajaran kooperatif yang dikembangkan oleh ahli pendidikan, seperti David and Roger Johnson. Penerapan syawir dalam pembelajaran PAI di Sekolah Berbasis Pesantren dapat dilakukan dengan beberapa tahapan, yaitu pembentukan kelompok, pemberian tugas, pengorganisasian kelompok, kolaborasi dan diskusi, pertanggungjawaban kelompok, evaluasi dan refleksi.